THE Effect of Listening to Asmaul Husna on Anxiety of Preoperative Patients in RSI Purwokerto : English - Wahyuni, Dwi; Sukmaningtyas, Wilis; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2023)
Background: Surgery is a medical treatment that uses invasive techniques by making an incision on the body part to be treated and ends with wound closure and suturing. This can cause both physiological and psychological stress. The psychological response to stress can be anxiety. This occurs because of the fear of bad possibilities that will happen that will harm the patient himself. Purpose: Knowing the effect of listening to Asmaul Husna on anxiety of preoperative patients at RSI Purwokerto. Methods: Design quasy experiment using Pretest-Posttest Control Group Design with sampling technique using purposive sampling technique as many as 116 respondents. The instrument used the Hamilton Anxiety Rating Scale (HARS). Data analysis using the Mann Whitney-U test. Results: We confirmed the effect of Asmaul Husna on anxiety. Paired T-test analysis of the control group with z= -0.37 with p = 0.70, while in the experimental group the mean ± SD was 0.27 ± 0.48 (CI 95% 0.14, 0.40) with p = 0.000. Mann Whitney-U analysis showed a value of z = -2.927, with p = 0.003. This shows that there is an effect of listening to Asmaul Husna on reducing the anxiety of preoperative patients at RSI Purwokerto. Conclusions: there is an effect of listening to Asmaul Husna on reducing anxiety of preoperative patients at RSI Purwokerto.